2016
DOI: 10.14411/fp.2016.019
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between host specificity and genetic diversity for the muscle-dwelling fish parasite Myxobolus pseudodispar: examples of myxozoan host-shift?

Abstract: Myxobolus pseudodispar Gorbunova, 1936 (Myxozoa) is capable of infecting and developing mature myxospores in several cyprinid species. However, M. pseudodispar isolates from different fish show up to 5% differences in the SSU rDNA sequences. This is an unusually large intraspecific difference for myxozoans and only some of the muscle-dwelling myxozoan species possess such a high genetic variability. We intended to study the correlation between the host specificity and the phylogenetic relationship of the para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…The present study appears to support the hypothesis that a pronounced potential for parasite diversification exists in hosts that underwent explosive speciation themselves (Gao et al., ; Pariselle, Morand, Deveney, & Pouyaud, ). Parasite diversification is likely fuelled by the high host specificity of myxozoans in their vertebrate hosts and, consequently, a greater possibility for successful host switching to, and radiation among closely related host species, especially sympatric Cypriniformes (Supplementary file ; Forró & Eszterbauer, ; Shin et al., ). Hence, apart from niche specialization in the host (clustering according to organ system) myxozoans clearly show host‐associated diversification mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The present study appears to support the hypothesis that a pronounced potential for parasite diversification exists in hosts that underwent explosive speciation themselves (Gao et al., ; Pariselle, Morand, Deveney, & Pouyaud, ). Parasite diversification is likely fuelled by the high host specificity of myxozoans in their vertebrate hosts and, consequently, a greater possibility for successful host switching to, and radiation among closely related host species, especially sympatric Cypriniformes (Supplementary file ; Forró & Eszterbauer, ; Shin et al., ). Hence, apart from niche specialization in the host (clustering according to organ system) myxozoans clearly show host‐associated diversification mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The intraspecific difference in small subunit ribosomal DNA (SSU rDNA) sequences is up to 5% even if the spore morphology and tissue preference is identical, which raises the possibility that M . pseudodispar is a species complex [ 15 ]. It was originally found to infect the common roach Rutilus rutilus [ 16 ], however, myxospores have been found in common bream Abramis brama , white bream Blicca bjoerkna , rudd Scardinius erythrophthalmus , bleak Alburnus alburnus and the European chub Squalius cephalus [ 15 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite our study showing some genetic diversity between the sequences obtained here from A. arcasii, P. duriense and those currently available in GenBank for this species, these values were consistent with previous molecular studies that addressed the high intraspecific variability found among different isolates of M. pseudodispar. This myxobolid was recently hypothesized to constitute a cryptic species complex, with genetic diversity explained by host-shift followed by ongoing processes of speciation in secondary hosts, and recombination of different lineages in oligochaete hosts (see [24]).…”
Section: Discussion Characterization and Identification Of The Myxobomentioning
confidence: 99%
“…Myxobolus pseudodispar is one of the most common muscle-dwelling parasites of leuciscids in Europe, having originally been described from roach Rutilus rutilus, and since then reported from several other species, including rudd Scardinius erythrophthalmus, freshwater bream Abramis brama, common bleak Alburnus alburnus, and white bream Blicca bjoerkna [24,54]. All these fish species were introduced into the Iberian Peninsula during the 20th century [28,35], where M. pseudodispar was reported to occur in several organs of the endemic species A. arcasii and P. polylepis, and the native species S. cephalus [10,25].…”
Section: Myxobolid Biodiversity In Endemic Iberian Cypriniformsmentioning
confidence: 99%
See 1 more Smart Citation